2017
DOI: 10.1080/00498254.2017.1405293
|View full text |Cite
|
Sign up to set email alerts
|

Efficient brain uptake of piperine and its pharmacokinetics characterization after oral administration

Abstract: 1. Piperine, the major biological active component in black pepper has been associated with miscellaneous pharmacological effects, especially on central nervous system. To correlate with its neurological activity, a comprehensive pharmacokinetic profile of piperine in brain, plasma and cerebrospinal fluid after oral administration in rats was investigated in this study. 2. It was noted that piperine could efficiently penetrate and homogeneously distribute into brain with similar pharmacokinetics profiles in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…[36] BBB permeability predictions for piperine and analogs from in vitro models and experimental permeability data from animal studies have shown that piperine diffuses into the brain after oral administration. [37,38] Given the evidence that both caffeine and piperine cross the BBB and are detectable in human milk after oral ingestion suggests that compounds that cross the BBB could be found in human milk and vice versa. Interestingly, the phenomenon of increased bioavailability of curcumin when piperine was co-administered did not lead to an abundance of curcumin in human milk.…”
Section: Discussionmentioning
confidence: 99%
“…[36] BBB permeability predictions for piperine and analogs from in vitro models and experimental permeability data from animal studies have shown that piperine diffuses into the brain after oral administration. [37,38] Given the evidence that both caffeine and piperine cross the BBB and are detectable in human milk after oral ingestion suggests that compounds that cross the BBB could be found in human milk and vice versa. Interestingly, the phenomenon of increased bioavailability of curcumin when piperine was co-administered did not lead to an abundance of curcumin in human milk.…”
Section: Discussionmentioning
confidence: 99%
“…Information on piperine serum or plasma levels observed in rats after oral administration is not uniform. With oral doses of 3.5, 20, 35 or 250 mg piperine/kg bw, corresponding plasma C max values of approximately 0.45, 3.4, 5.4-6.0 or 12.7 µmol piperine/L were observed in different studies [37,[41][42][43]. However, other studies observed higher C max values with approximately 9.9 µmol/L after an oral dose of 20 mg piperine/kg bw [44] or levels of approximately 28-39 µmol/L after a dose of 170 mg piperine/kg bw [34,36].…”
Section: Kinetics and Metabolismmentioning
confidence: 99%
“…However, other studies observed higher C max values with approximately 9.9 µmol/L after an oral dose of 20 mg piperine/kg bw [ 44 ] or levels of approximately 28–39 µmol/L after a dose of 170 mg piperine/kg bw [ 34 , 36 ]. Plasma protein binding was about 98% in rats receiving an oral dose of 35 mg piperine/kg bw [ 42 ]. Furthermore, piperine was shown to efficiently penetrate and homogeneously distribute into the brain of rats after oral piperine doses (35 mg/kg bw), leading to comparable AUC (0-∞) -values in brain and plasma with a brain–plasma AUC ratio of 0.95.…”
Section: Kinetics and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Group A: Vehicle control (VC) Group B: Diabetic control (STZ) Group C: Piperine treatment (STZ/PIP) Group D: Sitagliptin group (STZ/SITA) Both piperine (20 mg/kg/day) and Sitagliptin (25 mg/kg/day) were administered daily for 4 weeks during the course of the experiment. The dose of 20 mg/kg/day of piperine is considered the standard dose, also mentioned in the literature (Ren et al, 2018;Guo et al, 2020).…”
Section: Development Of Type -2 Diabetic Animal Model and Experimentamentioning
confidence: 99%